SIMULASI TRANSISI METAMORFOSIS BENTUK CITRA MODEL FRAKTAL DENGAN LIMA KOMPONEN KOLASE ARAH RADIAL DAN VERTIKAL - Rizki Zaki; Tedjo Darmanto; Riki Ramdan (STKIP PGRI Situbondo, 2024)
Metamorphic as a keyword has several implementations in digital era. The basic implementation is in image processing that can be extended to other fields. The metamorphic process in image processing as a series transition visualization of two source images can be simulated in fractal model. As long as a pair of fractal objects of the iterated function system model uses the affine coefficients as a result of transformations in initial state, so it can be transformed to other states easily just applying gradually manipulation on each set of coefficients based on the interpolation values between the source and destination objects. In this paper there are two kinds of metamorphic transition effects on two pairs of fractal objects with five collage components discussed. The first model exhibits the metamorphic transition effect in radial direction and the second one exhibits the metamorphic transition effect in vertical direction between the pair of similar objects.